Value design in optimal mechanisms - Anja Prummer; Francesco Nava (Johannes Kepler University of Linz, Department of Economics, 2023)
A principal allocates a single good to one of several agents whose values are privately and independently distributed, employing an optimal mechanism. The principal shapes the distribution of the agents' values within general classes of constraints. Divisive product designs, which are either highly favored or met with indifference, can simultaneously enhance surplus and diminish information rents by making agents' values more readily discernible. However, such designs also reduce competition among agents. Divisive designs are optimal under various design constraints, as the main drivers of revenue lie in increasing surplus and minimizing information rents, while competition plays a secondary role.
Keywords: D46; D82; L15; 330; Value Design; Mechanism Design; Differentiation